Методичні аспекти передбачення обсягів реалізації продуктових інновацій - Безпалько, Олена Вікторівна; Крайнюченко (Форноляк), Ольга Феодосіївна (My University, 2012)
Розглянуто різні методи передбачення обсягів реалізації продуктових інновацій. Приділено особливу увагу експертним моделям прогнозування з урахуванням споживчої поведінки. Рекомендовано використання епідеміологічних моделей в поєднанні з експертними методиками. Different methods of predicting sales volume of product innovation. Given special attention by expert forecasting model based on consumer behavior. Recommended use of epidemiological models in conjunction with expert techniques. Сonsidered different methods of predicting sales volume of product innovation. Given special attention by expert forecasting model based on consumer behavior. Recommended use of epidemiological models in conjunction with expert techniques.
Keywords: методи прогнозування; споживчий попит; потенціал ринку; число потенційних споживачів; коефіцієнт інновацій; коефіцієнт імітацій; метод стандартного розподілу ймовірностей; method forecasting; consumer demand; market potential; number of potential consumer; factor of innovations; factor of imitation; method of standard distribution of probabilities; кафедра економіки праці та менеджменту; кафедра маркетингу